Ejercicios de Integración por Partes

  Cálculo
$$\int{x^2e^x}dx$$ $$\int{-x^2sen(x)}dx$$ $$\int{ln(3x)}dx$$
$$\int{e^{2x}(x^2+2x+1)}dx$$

 

Desarrollo

  1. $\int{x^2e^x}dx$

Sean

$u=x^2$    y   $dv=e^xdx$

entonces

$du=2xdx$  y  $v=e^x$

$$\int{x^2e^x}dx=x^2\cdot e^x-\int{e^x\cdot 2x}dx\\=x^2\cdot e^x-2\int{e^x\cdot x}dx$$

nuevamente

$u=x$ y $dv=e^xdx$

entonces

$du=dx$ y $v=e^x$

de donde

$$x^2\cdot e^x-2\int{e^x\cdot x}dx=x^2\cdot e^x-2[xe^x-\int{e^x}dx]  \\  =x^2\cdot e^x-2x\cdot e^x+2\int{e^x\cdot x}dx\\=x^2\cdot e^x-2x\cdot e^x+2e^x+C$$


$\int{-x^2sen(x)}dx$

sean

$u=-x^2$. y $dv=sen(x)dx$

entonces

$du=-2xdx$ y $v=-cos(x)$

$$=x^2cox(x)-\int[-cos(x)\cdot -2xdx]=x^2cox(x)-2\int(x\cdot cos(x))$$

y, nuevamente

$u=x$ y $dv=cos(x)dx$

entonces

$du=dx$ y $v=sen(x)$

ordenando la idea

$$=x^2cox(x)-2[x\cdot sen(x)- \int(sen(x))]$$

$$=x^2cox(x)-2[x\cdot sen(x)- (-cos(x))]+C$$

$$=x^2cox(x)-2x\cdot sen(x)-2cos(x)+C$$


3.- $\int{ln(3x)}dx$

Sea. $u=ln(3x)$  y $dv=dx$

entonces

$du=\frac{1}{3x}\cdot 3dx=\frac{dx}{x} y $v=x$

por consecuencia

$$\int{ln(3x)}dx=ln(3x)\cdot x – \int {x\cdot\frac{dx}{x}}\\=xln(3x)-x+C$$


4.-     $\int{e^{2x}(x^2+2x+1)}dx$

Sean $u=x^2+2x+1$ y $dv=x^{2x}dx$

entonces

$du=2x+2$ y $v=\frac{e^{2x}}{2}$

se tendra que

$$=\frac{(x^2+2x+1)e^{2x}}{2}-\int{\frac{e^{2x}}{2}(2x+2}\\=\frac{(x^2+2x+1)e^{2x}}{2}-\int{(x+1)e^{2x}}dx$$

y ahora, sean:  $u =x+1$ y $dv=e^{2x}dx$

entonces $du=dx$ y $v=\frac{e^{2x}}{2}$

Reemplazando

$$=\frac{(x^2+2x+1)e^{2x}}{2}-\int{(x+1)e^{2x}}dx\\=\frac{(x^2+2x+1)e^{2x}}{2}-\left(\frac{(x+1)\cdot e^{2x}}{2}-\int{\frac{e^{2x}}{2}dx}\right)\\=\frac{(x^2+2x+1)e^{2x}}{2}-\left(\frac{(x+1)\cdot e^{2x}}{2}- \frac{1}{2}\frac{e^{2x}}{2} \right)\\=\frac{(x^2+2x+1)e^{2x}}{2}-\frac{(x+1)\cdot e^{2x}}{2}+\frac{e^{2x}}{4} +C \\=\frac{e^{2x}}{4}(2x^2+2x+1)+C$$

 

LEAVE A COMMENT